Care of Ebola Survivors and Factors Associated With Clinical Sequelae—Monrovia, Liberia. (21st September 2018) - de St. Maurice, A; Ervin, E; Orone, R; Choi, M; Dokubo, E K; Rollin, P E; Nichol, S T; Williams, D; Brown, J; Sacra, R; Fankhauser, J; Knust, B
Abstract: Background: The Eternal Love Winning Africa (ELWA) Clinic was the first clinic to provide free, comprehensive care to Ebola virus disease (EVD) survivors in Liberia. The objectives of this analysis were to describe the demographics and symptoms of EVD survivors at ELWA from January 2015 through March 2017 and to identify risk factors for development of sequelae. Methods: Patients' demographic and clinical information was collected by chart review in June 2016 and March 2017. Associations with clinical sequelae were analyzed using the chi-square test, t test, and multivariate logistic regression. Results: From January 2015 to March 2017, 329 EVD survivors were evaluated at ELWA. Most survivors experienced myalgia/arthralgia (73%; n = 239) and headache (53%; n = 173). The length of time from Ebola Treatment Unit (ETU) discharge to first clinic visit ranged from 0 to 30 months. Many visits (30%) occurred 24 or more months after ETU discharge. The proportion of visits for headache, weight loss, joint pain, visual problems, insomnia, fatigue, memory loss, decreased libido, depression, and uveitis decreased over time. More men than women had visits for depression; however, these differences were not significant. Symptom prevalence differed in adults and children; significantly more adults experienced myalgia/arthralgia (77% vs 44%), visual problems (41% vs 12%), post-EVD-related musculoskeletal pain (42% vs 15%), and insomnia (17% vs 2%). Conclusions: EVD survivors frequented ELWA for EVD-related symptoms many months after ETU discharge, indicating a long-term need for care. Reported symptoms changed over time, which may reflect eventual resolution of some sequelae.